Validation of a Hypothesis: Colonization of Black Smokers by Hyperthermophilic Microorganisms - Wirth, Reinhard; Luckner, Manja; Wanner, Gerhard (Frontiers in Microbiology, 2018)
Newly erupted black smokers (hydrothermal vent chimneys) are sterile during their formation, but house hyperthermophilic microorganisms in substantial amounts in later stages. No direct experimental data exist by which mechanisms hyperthermophiles colonize newly erupted black smokers, but a scenario was proposed recently how this might happen. Here we combine high temperature light microscopy with electron microscopy to show that two hyperthermophilic Archaea, namely Pyrococcus furiosus and Methanocaldococcus villosus are able to adhere onto authentic black smoker material (BSM). We especially are able to directly observe the adhesion process via video recordings taken at high temperatures. These data validate the hypothesis that hyperthermophiles are transferred by serendipitous water currents to the outside of newly formed black smokers and react within seconds to the there prevailing high temperatures by very fast movements. They scan the surface of the hydrothermal chimneys via a much slower zigzag seek-movement and adhere via their flagella at a suitable place, building up biofilms.